Market Reaction Before and After the Pandemic - Deni Juliasari; Fetri Setyo Liyundira; Retno Cahayaningati (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
Indonesia's economic situation, such as the JCI, Rupiah exchange rate, inflation, and interest rates, will be affected by the pandemic. Therefore, this study aims to understand the impact of JCI, the Rupiah exchange rate, inflation, and interest rates before and after the pandemic. This type of research uses event studies. Analysis used analysis of variance (ANOVA) F-difference test and sampling technique used objective sampling. The company's sampling criteria are as follows: 1. JCI is closed daily for 7 days before the event and 7 days after the event. 2. Rupiah exchange rate for 7 days before the event and 7 days after the event. 3. Seven months before and after the inflation event. 4. 7-month interest rates before and after the event. JCI before and after are the same and the average difference in the JCI descriptively between the JCI is not significantly the same as the rupiah exchange rate, while inflation and average interest rates show differences before and after the announcement of the Covid 19 pandemic.